Data Visualization on Zakat Distribution Among UiTM Students in UiTM Selangor - Nurdin, Sitti Rezkinaah; Redzuan, Fauziah; Abdul Majid, Rogayah; Abd Karim, Norisan (Journal of Advanced Research Design, 2025)
Zakat, one of Islam’s five pillars, plays a significant role in alleviating financial hardship, especially among Universiti Teknologi MARA (UiTM) students, many of whom come from low-income families. However, the current Zakat distribution faces challenges such as limited transparency and low awareness, hindering stakeholders’ ability to make informed, data-driven decisions. This research addresses the issue by developing a Zakat distribution data visualization dashboard using Jupyter Notebook, MySQL, and Power BI. The system provides interactive visualization tools that highlight patterns, trends, and disparities in Zakat allocation, thereby enabling administrators, researchers, and the public to better understand its impact. By leveraging advanced analytics, the dashboard offers a user-friendly interface to explore complex data, enabling a deeper understanding of zakat distribution flows. The project utilizes the OSEMN framework and Agile methodology to ensure systematic data handling, analysis, and visualization. This initiative empowers zakat distribution with valuable insights, facilitating informed decision-making and resource allocation. To further optimize the dashboard, we suggest expanding its scope to include data from all UiTM campuses, enabling a comprehensive analysis of zakat distribution patterns in UiTM.